2013
DOI: 10.14260/jemds/1072
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Psoas Minor Muscle - Reviewed

Abstract: Psoas minor (PM) muscle belongs to the category of vestigial muscles. It is large in size in all those quadrupeds that brachiate and leap or run at very fast speed. None of these functions being required in bipedal, plantigrade man the muscle has receded during evolution; hence it is present only in 40-60% population. Apart from racial variations, a large number of morphological variations of this muscle have been described in the literature. The present study has been conducted in 20 cadavers. Psoas minor mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In cats, the muscle is active when the back is arched [9]. Although it has declined and is now only a remnant in humans, its presence remains crucial in maintaining posture and hip flexion in athletes [1,3]. The cumulative incidence of PMi varies depending on the race and ethnicity of the study population [22] and when present, it tends to shows several variations in morphology and morphometry.…”
Section: Discussionmentioning
confidence: 99%
“…In cats, the muscle is active when the back is arched [9]. Although it has declined and is now only a remnant in humans, its presence remains crucial in maintaining posture and hip flexion in athletes [1,3]. The cumulative incidence of PMi varies depending on the race and ethnicity of the study population [22] and when present, it tends to shows several variations in morphology and morphometry.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PMM is also vital in some professions such as sports, and it might get injured during certain activities. 6 In some sports, inguinal pain arises from the strained thin tendon of PMM, which results from hyperextension of the hip joint, where both feet off the ground tense the muscle-tendon. In such cases, if the pain is spread to the abdominal wall and perineum, it would be a cause of psoas minor syndrome.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…2 The extant literature did not offer a clear view of PMM distal attachment variations. 5,6 The sports medicine field reports accounts of the muscle's clinical significance. 6 The previous studies revealed some morphological and racial variations.…”
mentioning
confidence: 99%
See 1 more Smart Citation